Syarifah Sungai Raya Aceh Timur: Marriage and the Struggle to Find Identity - Juliandi, Budi; Zulfikar, Zulfikar; Mudrika, Syarifah (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
Every society has its own characteristics and identity that distinguish them from the others. Their diverse backgrounds form different views. This study explores the struggle to find Syarifah's identity in Sungai Raya Aceh Timur, related to their marriage. This study is an empirical legal research that examines the application of law in the reality of society. The data collection technique used is by conducting in-depth interviews, observations and literature studies related to the discussion of marriage. This study concludes that most Syarifah Sungai Raya believe in the doctrine of Sayyid-Sharifah endogamy marriage. However, some cannot deny the fact that exogamous marriages also occur. The doctrine of endogamous marriage raises a new awareness of their identity as zurriyyat of the Prophet PBUH. Because of this, exogamous marriage is a last resort when the goal of endogamous marriage cannot be met.